Pengembangan E-Book Pengelolaan Lab Bidang Studi Pada Mahasiswa Tata Boga Unesa - Handajani, Sri; Nurfatimah, Ratna Palupi; Astuti, Nugrahani; Lukitasari, Febriani (Abimanyu: Journal of Community Engagement, 2025)
The purpose of this study is to formulate an interactive E-Book as a learning resource for Culinary Arts students enrolled in the Laboratory Management course at the State University of Surabaya (UNESA). The E-Book was developed utilizing the ADDIE approach (Analysis, Design, Development, Implementation, and Evaluation), which assures that the design, implementation, and evaluation processes are organized and systematic. The findings of this study show that the learning resource effectively accommodates students' academic needs while also increasing their interest and grasp of laboratory management topics. Validation by subject matter and media specialists resulted in high average scores in design, substance, and utility categories. Furthermore, studies including students received great feedback, with an average assessment score of more than 80%, putting the E-Book in the "excellent" category.